Effectiveness of the Inspectorate in Supervising Financial Management at the Secretariat of the Regional House of Representatives (DPRD) of Lebak Regency - Rudini Rudini; A. Masrich; Baharudin Thahir (Sean Institute, 2026)
This study is motivated by issues related to the effectiveness of the Inspectorate’s supervision of financial management at the Secretariat of the DPRD of Lebak Regency, particularly the persistent gaps between regulations, administrative practices, and governance integrity. Various findings such as delays in audit follow-up and excess travel-payment cases indicate the need for a comprehensive evaluation of the regional internal oversight function. The research employs a descriptive qualitative approach based on an input process output outcome paradigm. Data were collected through interviews with eight key informants, observations, and a review of financial documents and regulatory frameworks. The theoretical framework refers to Richard M. Steers’ organizational effectiveness theory, which encompasses four main dimensions. Research instruments include in depth interviews, document analysis, and thematic analysis using Robert K. Yin’s case study model. The results show that the effectiveness of the Inspectorate remains suboptimal across all dimensions. Organizationally, the number of auditors and the support of financial information systems remain inadequate. Environmentally, unit-level resistance and political pressure weaken supervisory independence. The worker dimension reveals gaps in competence and integrity. Meanwhile, the management dimension demonstrates weak follow-up mechanisms, suboptimal monitoring, and limited technology based innovations. These conditions contribute to recurring findings, slow resolution of excess payments, and limited public transparency. The study concludes that strengthening human resources, enhancing institutional independence, digitizing audit systems, and enforcing follow-up mechanisms are strategic steps needed to improve supervisory effectiveness.